MutSβ regulates G4-associated telomeric R-loops to maintain telomere integrity in ALT cancer cells - Sakellariou, Despoina; Bak, Sara Thornby; Isik, Esin; Barroso, Sonia I; Porro, Antonio; Aguilera, Andrés; Bartek, Jiri; Janscak, Pavel; Peña-Diaz, Javier (Cell reports, 2022)
Up to 15% of human cancers maintain their telomeres through a telomerase-independent mechanism, termed "alternative lengthening of telomeres" (ALT) that relies on homologous recombination between telomeric sequences. Emerging evidence suggests that the recombinogenic nature of ALT telomeres results from the formation of RNA:DNA hybrids (R-loops) between telomeric DNA and the long-noncoding telomeric repeat-containing RNA (TERRA). Here, we show that the mismatch repair protein MutSβ, a heterodimer of MSH2 and MSH3 subunits, is enriched at telomeres in ALT cancer cells, where it prevents the accumulation of telomeric G-quadruplex (G4) structures and R-loops. Cells depleted of MSH3 display increased incidence of R-loop-dependent telomere fragility and accumulation of telomeric C-circles. We also demonstrate that purified MutSβ recognizes and destabilizes G4 structures in vitro. These data suggest that MutSβ destabilizes G4 structures in ALT telomeres to regulate TERRA R-loops, which is a prerequisite for maintenance of telomere integrity during ALT.
Keywords: mismatch repair; telomere; Neoplasms; CP: Molecular biology; CP: Cancer; R-Loop Structures; RNA dlouhá nekódující; ALT cancers; RNA, Long Noncoding; Telomere Homeostasis; lidé; Humans; telomery; C-circle; G-quadruplex; DNA; nádory; homeostáza telomer; R-loop; Telomere; R-smyčka